Я тебя урою: [роман] / Владимир Колычев - Колычев Владимир Григорьевич (Русский шансон, 2007)
Экземпляры: аб (20231107) / Инвентарный номер: 59731 / Цена: 80.00 / Сис.шифр: Р2 / Авт.знак: К 61 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6